Short-and Long-Term Clinical Outcomes of Infliximab in Fulminant Ulcerative Colitis. (21st December 2010) - Florholmen, J.; Øverland, G.; Olsen, T.; Rismo, R.; Cui, G.; Christiansen, I.; Paulssen, E. J.; Goll, R.
Abstract : The aim was to characterize short- and long-term clinical outcomes of infliximab in fulminant ulcerative colitis. Patients with severe ulcerative colitis meeting the criteria of fulminant colitis after 3 days of glucocorticosteroid treatment were randomized to control or additional induction therapy of infliximab followed by an on demand/maintenance therapy of infliximab. Twenty six patients with fulminant colitis were equally randomized. At Day 7, ten patients in the control group and none in the infliximab group were in the need of colectomy (P < .001 ). Due to superior effect of infliximab, patients in the control group were of ethical reasons transformed to infliximab treatment instead of performing colectomy. The probability to avoid colectomy was 0.66 with a median observation time of 52 months and a maximal of 91 months. The addition of azathioprine reduced the risk of late colectomy. We conclude that infliximab is effective in preventing early and late colectomy in fulminant colitis.